DOSE-DEPENDENT EFFECTS OF DIPYRIDAMOLE IN PATIENTS WITH CONGESTIVE HEART FAILURE - M. P. Savenkov; M. V. Borshevskaya; S. N. Ivanov; T. V. Belkina; V. I. Buvaltsev; M. N. Palkin (Российский кардиологический журнал, 2001)
We have practiced courses of treatment with dipyridamol (Curantil, Berlin-Chemie), 25 to 225 mg daily, 1-3 months long, in 55 patients with congestive heart failure NYHA III-IV class in conjuction with baseline treatment with ACE inhibitors, prolonged nitrates and diuretics. Treatment efficacy was controlled by thromboelastography, ADP-induced platelet aggregation and bifunctional daily BP and ECG monitoring. A dose-dependent and modulating antiaggregating effect of dipyridamol has been shown in the study. The usage of 225 mg Curantil daily (75 mg 3 times a day) resulted in an antiaggregating action in the first day, however, it was characterized by a higher risk of hypotension with concomitant baseline vasodilating therapy. Considerable antiaggregating effect of 75 mg Curnatil daily (25 mg 3 times a day) and 50-25 mg daily developed by the end of the first and, respectively, second week of treatment; the risk of arterial hypotension was non-significant. We conclude that for long-term prevention in patients with CHF administration of Curantil 75-25 mg daily is preferable. Determining individual sensitivity to the chosen dose (by BP dynamics) is rational before initiating the treatment.